Population genetics of immune-related multilocus copy number variation in Native Americans. Issue 128 (29th March 2017) - Zuccherato, Luciana W.; Schneider, Silvana; Tarazona-Santos, Eduardo; Hardwick, Robert J.; Berg, Douglas E.; Bogle, Helen; Gouveia, Mateus H.; Machado, Lee R.; Machado, Moara; Rodrigues-Soares, Fernanda; Soares-Souza, Giordano B.; Togni, Diego L.; et al.
Abstract : While multiallelic copy number variation (mCNV) loci are a major component of genomic variation, quantifying the individual copy number of a locus and defining genotypes is challenging. Few methods exist to study how mCNV genetic diversity is apportioned within and between populations (i.e. to define the population genetic structure of mCNV). These inferences are critical in populations with a small effective size, such as Amerindians, that may not fit the Hardy–Weinberg model due to inbreeding, assortative mating, population subdivision, natural selection or a combination of these evolutionary factors. We propose a likelihood-based method that simultaneously infers mCNV allele frequencies and the population structure parameter f, which quantifies the departure of homozygosity from the Hardy–Weinberg expectation. This method is implemented in the freely available software CNVice, which also infers individual genotypes using information from both the population and from trios, if available. We studied the population genetics of five immune-related mCNV loci associated with complex diseases (beta-defensins, CCL3L1/CCL4L1, FCGR3A, FCGR3B and FCGR2C ) in 12 traditional Native American populations and found that the population structure parameters inferred for these mCNVs are comparable to but lower than those for single nucleotide polymorphisms studied in the same populations.